Können geflügelte Worte "wissenschaftlich" sein, oder gehören sie ins Raritätenkabinett? Eine Diskussion anlässlich zweier Neuerscheinungen - Farø, Ken (HERMES - Journal of Language and Communication in Business, 2005)
How are we to understand and deﬁne stock quotations (Germ. geﬂügelte Worte, Dan. bevingede ord)? This is in my view far too important a task to leave to the publications collecting a highly interesting but nevertheless often heterogenous material under the header of this term. The material published does, so it seems, often not meet the require ments of this linguistic category when systematically deﬁned. Two basic criteria must in my view be fulﬁlled if we are to speak of stock quotations: (1) the speech act citation (in broad terms) must be a genuine feature of the linguistic unit, and (2) the lexeme must be lexicalized. Other features such as polylexical structure and modiﬁcation may be optional but they should, I suggest, not be seen as obligatory. Stock quotations are both a lexical as well as a highly pragmatic category as their genuine purpose is to perform a speciﬁc speech act. The discussion of stock quotations is undertaken on the grounds of two new dictionaries of this category, i.e. the German Büchmann (2002) and the Danish Bramsen (2001). Stock quotations do − in spite of what is claimed in one of these dictionaries − in fact lend themselves to scientiﬁc description.